Analisis Return on Investment (ROI) Digital pada UMKM: Sebuah Pendekatan Metodologis - Riezky Amalia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
As productive economic enterprises owned by individuals or individual business entities, MSMEs are faced with the reality where digital technology is developing increasingly rapidly, which forces them to immediately carry out digital transformation to achieve business growth and sustainability. Investments in digital technology, from digital marketing to the use of e-commerce platforms, have become important to maintain the competitiveness of MSMEs in an increasingly competitive market. In carrying out digital transformation, MSMEs need to measure and assess the performance of digital investments by comparing the profits obtained from the investment against the costs incurred in the process of digitizing their business. This is the main challenge faced by MSMEs in measuring the effectiveness of their digital investments. This is where the concept of Return on Investment (ROI) becomes very relevant. In this research, it was found that calculating digital ROI requires careful planning and continuous evaluation so that MSMEs can make the right decisions regarding the technology they invest in, both short-term and long-term calculations. Increasing ROI requires a strategic approach that involves reducing costs, increasing revenue, monitoring performance, and utilizing technology and automation that is appropriate to the business being run, through a combination of digitalization strategies, product innovation, good customer service, operational efficiency, and creative marketing. By optimizing every element in investment, it is ensured that every rupiah invested provides maximum returns. By implementing these strategies, MSMEs can increase their competitiveness in the market, strengthen relationships with customers, to increase the competitiveness and sustainability of their business.